Pengaruh Problem Based Learning Berbantuan Media Chemcollective pada Materi Larutan Penyangga Terhadap Keterampilan Berpikir Kritis Siswa Kelas XI SMAN 1 Narmada - Nia Febrianti; Yayuk Andayani; Mukhtar Haris (Chemistry Education Practice, 2025)
This study aims to explain the effect of media-assisted problem-based learning using ChemCollective on buffer solution material on the critical thinking skills of 11th grade students at SMAN 1 Narmada. This quasi-experimental study used a nonequivalent control group design and was conducted in classes XI F5 and XI F6 with a total of 72 students. Cluster sampling was used as the sampling technique. The determination of the experimental class and control class was based on the lower average pretest score as the experimental class and the higher score as the control class. The pretest results obtained in class XI F5 were 53.44 and class XI F6 were 59.69, so class XI F5 was the experimental class and class XI F6 was the control class. The data collection technique used a two-tier multiple-choice test instrument. The results showed that the average N-Gain score was 0.6 in the experimental class and 0.34 in the control class, both of which were in the moderate category. The t-test result obtained was tcount (4.25) > ttable (1.994), so Ho was rejected and Ha was accepted. It can be concluded that the use of media-assisted problem-based learning chemcollective on buffer solution material had an effect on improving the critical thinking skills of grade XI students at SMAN 1 Narmada.